Development Of Flip Book Media For Sports And The Value Of Patriotism - Haryanto, Andung Dwi; Nugroho, Dicky Anggriawan; Ylsan, Dheandra Tsabitha (STAMINA, 2025)
Physical education, sports and health should be implemented creatively and comprehensively. Learning not only emphasizes psychomotor aspects, but understanding the material provided is also important. Sports courses, conventionally considered the domain of physical activity, are now getting a touch of digital technology to make them more relevant and interesting. As technology develops, the entry of dominant foreign cultures causes a decline in love for local culture. In the era of globalization, the spirit of patriotism has decreased in line with the weakening of love for the country. Patriotism can be realized in one way through sport, where sport plays a role in the construction and reproduction of national identity. This research aims to develop flip book-based learning media to help understand sports and the value of patriotism. The research method used is the research and development (R&D) method. The product designed is a sports flipbook learning media that can be used on smartphones or computers. The development model used is the ADDIE development model, namely: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. Quantitative data analysis techniques use descriptive statistics, and qualitative data uses content analysis techniques. The results of the research show that sports flipbook media has been produced which contains text, images and videos of sports material and patriotism values. As a result of understanding sports material, the average test score increased from 65 to 85, sports practical skills, the average score increased from 70 to 88, and understanding the value of patriotism, the average score increased from 60 to 83